2022
DOI: 10.3390/biom12121747
|View full text |Cite
|
Sign up to set email alerts
|

Gαs-Coupled CGRP Receptor Signaling Axis from the Trigeminal Ganglion Neuron to Odontoblast Negatively Regulates Dentin Mineralization

Abstract: An inflammatory response following dental pulp injury and/or infection often leads to neurogenic inflammation via the axon reflex. However, the detailed mechanism underlying the occurrence of the axon reflex in the dental pulp remains unclear. We sought to examine the intracellular cyclic adenosine monophosphate (cAMP) signaling pathway in odontoblasts via the activation of Gs protein-coupled receptors and intercellular trigeminal ganglion (TG) neuron–odontoblast communication following direct mechanical stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…NCXs and PMCAs in odontoblasts are functionally coupled with high pH stimulation-induced Ca 2+ mobilization, which is important for physiological and high-pH-induced dentinogenesis ( Kimura et al, 2016 , 2021 ). Our recent results also indicate “retrograde” communication between neurons and odontoblasts via neuropeptides, such as calcitonin gene-related peptide (CGRP), released from nerve terminals (i.e., axon reflex) during neurogenic inflammation in the dental pulp ( Saito et al, 2022 ).…”
Section: Discussionmentioning
confidence: 93%
“…NCXs and PMCAs in odontoblasts are functionally coupled with high pH stimulation-induced Ca 2+ mobilization, which is important for physiological and high-pH-induced dentinogenesis ( Kimura et al, 2016 , 2021 ). Our recent results also indicate “retrograde” communication between neurons and odontoblasts via neuropeptides, such as calcitonin gene-related peptide (CGRP), released from nerve terminals (i.e., axon reflex) during neurogenic inflammation in the dental pulp ( Saito et al, 2022 ).…”
Section: Discussionmentioning
confidence: 93%
“…In contrast to findings that CGRP directly promotes the proliferation and osteogenic differentiation of bone marrow mesenchymal stem cells via the Wnt/β‐catenin signalling pathway (Jia et al., 2019; Wan et al., 2021), CGRP exhibits an inhibitory effect on DPSC proliferation and does not affect differentiation of DPSCs (Michot et al., 2020; Moore et al., 2022). An odontoblast‐neuron co‐culture study also revealed that CGRP signalling negatively regulates dentinogenesis as a defensive mechanism (Saito et al., 2022), which suggests that CGRP exerts different effects on different types of stem cells. Hence, CGRP may act on other components in the local microenvironment to promote healing in the dental pulp.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance, our results showed that NF-H-positive TG cells are Gα s protein-positive. In our previous study, we reported CGRP release from peptidergic C neurons of TG, but not NF-H-positive neurons, into the extracellular space following mechanical stimulation of the neurons [ 22 ].…”
Section: Discussionmentioning
confidence: 99%